2021
DOI: 10.29337/ijsp.146
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Clinical Trial Protocol about the Impact of Family-Based Multimedia Education Based on Telephone Tracking (Tele Nursing) to Improve the Quality of Life and Self-Efficacy in Patients with Myocardial Infarction

Abstract: Background: Provision of education to a person with myocardial infarction and an active family member, who takes care of the patient can prevent or delay the onset of the disease. Telephone tracking is a very useful and inexpensive way to assess the patients’ needs and help them with their care problems. This clinical trial (interventional) protocol was conducted over the impact of family-based multimedia education based on the telephone tracking (tele-nursing) to improve the quality of life and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…It is also worth noting, these results supported other studies and confirmed that average self-efficacy scores in the study group were significantly enhanced after telephone follow-up empowerment program (Javanmardifard, Ghodsbin & Kaviani, 2017;Madadkar Dehkordi, et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is also worth noting, these results supported other studies and confirmed that average self-efficacy scores in the study group were significantly enhanced after telephone follow-up empowerment program (Javanmardifard, Ghodsbin & Kaviani, 2017;Madadkar Dehkordi, et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Lack of participation in self-management behaviors or failure to control cardiac risk factors leads to poor health outcomes, frequent readmissions, increased mortality rates, and a higher burden of health service costs. (Madadkar Dehkordi, Okhovat & Karimiankakolaki, 2021). Accordingly, it is imperative to develop an effective nursing intervention that supports myocardial infarction patients to properly manage their disease.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The health industry uses telenursing, an information and communication technology system, to offer long-distance nursing and care services. 8 Instead of having face-to-face meetings, patients and their caregivers communicate through media made available to patients and their families. Many care domains can benefit from the application of telenursing practices, such as home visits; secure email messaging systems with hotline support; discharge planning; chronic telenursing in the department; telenursing for illnesses and emergencies, including outpatient care; call center services; triage; and discharge planning.…”
Section: Introductionmentioning
confidence: 99%